Early Care and Education for Children in the Child Welfare System: Evaluations of Two Training Programs. Issue 2 (14th March 2016) - Klein, Sacha M.; Falconer, Mary Kay; Benson, Stephanie M.
Abstract : Despite evidence that early care and education services benefit at-risk children, they remain underutilized by families in the child welfare system. This article describes two training programs developed to educate child welfare and childcare/preschool staff about the importance of early care and education for maltreated children and how to access these services. A combined total of 274 trainees completed knowledge tests about this topic and significant pre- to post-training improvements indicate that both training programs effectively increased participants' knowledge about this important topic. In addition, improvement in self-assessed competency was observed for participants in one program, and positive changes in attitudes and anticipated practice behavior regarding childcare for foster children were observed among participants in the other.